Shortcomings in Financial Risk-modeling as a Factor in Financial Crisis - Kovár, Peter; Havlíček, David, 1985-; Baran, Jaroslav; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2012)
In this bachelor's thesis we explore research on the importance of inclusion the factor of liquidity into risk-measuring and asset-pricing models. We also illustrate the price impact of liquidity shocks on major stock-exchange indices during the financial crisis of 2008. We look at the changes addressing the issue of liquidity in currently proposed Basel III regulation and identify some of the potential pitfalls therein. Presenting a case study, we evaluate whether these provisions would have been sufficient to stave off the bankruptcy of Lehman Brothers, Inc. We also investigate the role of complexity behind newly designed financial derivatives products and the risk associated from badly managed securitization process.
Vedoucí práce: David Havlíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses